Application of Regional Regulations on Public Order in Handling Homeless and Beggars - Alhimny Fitrah Janu; Mutia Cherawaty Thalib; Abdul Hamid Tome (Estudiante Law Journal, 2023)
The purpose of this research is to find out what is the effectivenesstackling homeless and beggars in Gorontalo City based on Article 23 of Regional Regulation No. 1 of 2018 concerning Public Order. Then also to know and explain what are the factors that hinder the handling of homeless people and beggars. The results of the study show that the prevention of homeless people and beggars in Gorontalo City has not been effective. This is due to the fact that the efforts being made are limited to repressive efforts by using the Civil Service Police Unit as a government apparatus based on the Gorontalo City Regional Regulation Number 1 of 2018 concerning Public Order. Then the factors that hinder the handling of homeless and beggars are divided into internal factors, including: limited operational costs, lack of facilities and infrastructure, lack of agencies involved, and leakage of information to the public. The external factors are: the presence of persons coordinating the homeless and beggars, and the habit of the people who like to give.